(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the military potential of the nomadic tribes who lived in the Aral Sea region during the archaic and ancient times, defense processes, the first states in Central Asia, the Iranian-Achaemenids, Alexander the Great, the Seleucids, the political, socio-economic processes with the Greco-Bactrian states, military preparation is covered.